Incidence and Geographic Distribution of Extensively Drug-Resistant Tuberculosis in KwaZulu-Natal Province, South Africa - Lim, Jennifer R.; Gandhi, Neel R.; Mthiyane, Thuli; Mlisana, Koleka; Moodley, Julie; Jaglal, Prenika; Ramdin, Neeshan; Brust, James C. M.; Ismail, Nazir; Rustomjee, Roxana; Shah, N. Sarita (PloS one, 2015)
South Africa is experiencing a widespread drug-resistant tuberculosis epidemic, although data are limited regarding the current situation. This study finds that the extensively drug-resistant tuberculosis (XDR-TB) incidence in KwaZulu-Natal increased to 3.5 cases/100,000 (776 cases) in 2011-2012. XDR-TB cases are widely distributed geographically, with the majority of districts experiencing a rise in incidence.